The Effect of Educators' Pedagogical Competence on the Critical Thinking Ability of Equivalency Education Learners - Novitasari, Nimas; Shofwan, Imam (Universitas Negeri Semarang, 2024)
Entering the era of scientific and technological transformation in the 21st century, education is an important element to produce competent future generations. Competencies that must be possessed include communication, collaboration, critical thinking, and creativity. The increase in competence is directly proportional to the quality of the nation's next generation with the ability to survive in global competition. This study aims to determine the effect of educators' pedagogical competence on the critical thinking skills of package C students at SKB Ungaran Semarang Regency. This type of research is quantitative research by applying the ex post facto method. The population used was educators and students while the sample of this study was educators and students of package C, a total of 30 people each with saturated sampling technique. Data collection in this study used questionnaire techniques. The results showed t count 3.045 > 1.697 with a significance value of 0.005 < 0.05 so, it was stated that there was an influence between pedagogical competence on critical thinking skills. The coefficient of determination obtained is 0.249, which means that the critical thinking ability of students is influenced by the pedagogical competence of educators by 24.9%. Therefore, educators can have a positive influence on students in creating a competitive generation.